Identification of Critical Success Factor Startup in Business Incubators (Case Study: Bandung Techno Park) - Sisca Eka Fitria; Faris Rahman Hakim (International Journal of Social Service and Research, 2022)
The growth of startups in Indonesia has been relatively fast since the last few years. Startup growth must be accompanied by knowledge related to critical success factors for the success of startup. Bandung Techno Park serves an incubator to help develop startups toward success. This research aims to find out the critical success factors of startups in Bandung Tecno Park. Grand theory in this study is entrepreneurship and the applied theory is a critical success factor. This research examies innovation, entrepreneurship, technology and economics as critical success factor of startups. Research methods in this study use qualitative research methods with descriptive analysis. Data obtained in-depth interviews with CEOs and startup experts in Bandung Techno Park. The data analysis techniques used are data collection, data reduction and data conclusion. The result of this study show that Innovation is one of the startup needs that must be met so that startups continue to grow and continue to be acceptable to the market. In implementation of innovation, obstacles that are often encountered in innovating are related to market targets, capital resources, technological trends, and human resources. Entrepreneurship is one of the concepts that must be understood and owned by a CEO in order to be able to run his business well. Technology is a tool that cannot be separated from startups. Startups always need technology, but technology skills of the operators are needed more than the latest technology. Economist, deals with funding including investors and financial management. Things to note related to funding are how to attract investors, maintain investor contracts and manage finances wisely. Of these four factors, entrepreneurship is the most important factor in startup success. This aspect of entrepreneurship is related to the characteristics of the founder, and the performance of human resources